Choroidal metastasis from granulocyte colony‐stimulating factor‐producing esophageal squamous cell carcinoma: a case report. Issue 4 (23rd February 2017) - Fukuda, Shuichi; Fujiwara, Yoshinori; Mishima, Hiroshi; Wakasa, Tomoko; Hanamoto, Hitoshi; Inoue, Keisuke; Kitani, Kotaro; Ishikawa, Hajime; Tsujie, Masanori; Yukawa, Masao; Okajima, Kaoru; Ohta, Yoshio; et al.
Key Clinical Message: Granulocyte colony‐stimulating factor (G‐CSF)‐producing esophageal squamous cell carcinoma (ESCC) is rare. Esophageal cancer is a highly aggressive disease and often spreads hematogenously; however, choroidal metastases are rarely seen. This report detailed an extremely rare case of G‐CSF‐producing ESCC with choroidal metastasis. Abstract : Granulocyte colony‐stimulating factor (G‐CSF)‐producing esophageal squamous cell carcinoma (ESCC) is rare. Esophageal cancer is a highly aggressive disease and often spreads hematogenously; however, choroidal metastases are rarely seen. This report detailed an extremely rare case of G‐CSF‐producing ESCC with choroidal metastasis.